An experiment on electromechanical power steering (EPS) system of a CAR - Akhtaruzzaman, Md.; Mohd Razali, Norrul’ Aine; Rashid, Muhammad Mahbubur; Shafie, Amir Akramin (International Association of Computer Science and Information Technology, 2010)
This paper describes an experiment on Electromechanical Power Steering (EPS) system of a car.Nowadays EPS system can be considered as a Mechatronics system that reduces the amount of steering effort by directly applying the output of an electric motor to the steering system.In this paper, the constitutions, operational mechanism and control strategies of EPS system are introduced. A potentiometer measures driver input to the steering wheel,both direction and rate of turn. This information is fed into a microcontroller that determines the desired control signals to the motor to produce the necessary torque needed to assist. Although an electro hydraulic power assisted steering system can be used to reduce the fuel consumption, but the maximum benefit can be obtained if electronic system is applied instead of the hydraulic mechanism. The paper shows that a good power steering control technique is achieved by designing a Mechatronics system. The experimental results for the designed EPS are also analyzed in this paper.